Antioxidants and total polyphenols of a black chocolate whit incorporation of unroasted cocoa (Theobroma cacao L.) - Chacón Ortiz, Clorinda Yordana (2021)
Cocoa and its main derivative, chocolate, are an important source of antioxidant compounds for human nutrition. Polyphenols are the main antioxidants present in chocolate and are affected by the industrialisation processes of cocoa beans. In this regard, the effect of incorporating raw cocoa during the final stage of the refining process on the antioxidant capacity and phenolic content of dark chocolate was studied. For this purpose, dark chocolates (70%) were made with the incorporation of raw cocoa paste (10, 20 and 30% w/w) in the final refining stage. The antioxidant capacity of all the treatments was determined by the DPPH (2,2-Diphenyl-1-picrylhydrazyl) method and the total phenolic content by the Folin Ciocalteu spectrophotometric method. It was observed that the incorporation of raw cocoa significantly increases the content of antioxidants and total polyphenols in chocolate. As the dose of raw cocoa increases, the antioxidant activity of the chocolate increases linearly (R2=0.996); on the other hand, the polyphenol content increases exponentially (R2=0.968). Only the lowest dose (10%) doubles the phenolic content and the ratio decreases with higher doses of incorporation. The results suggest that the incorporation of raw cocoa in the formulations makes it possible to obtain chocolates with high phenolic content, improving the technological processes for using cocoa produced in the tropical Andes to develop bioactive chocolates, in line with new consumer demand.